O papel do environmental social and governance e dos objetivos do desenvolvimento sustentável nas universidades do ranking UI GreenMetric - Kieling, Débora Londero (2022)
The environmental and social impacts caused by man are diverse, which indicates the need to recognize Sustainable Development (SD) as a solution to the existing adversities. In society, universities that already have a significant role in the training of professionals, also stand out 28 for promoting sustainability in their operations and contribute actively in society, besides performing several internal actions aimed at teaching, research, extension, management, operation and external actions aimed at the Environmental Social and Governance (ESG) and the Sustainable Development Goals (SDG). Given the above, the general objective of this study is to verify the application of ESG in universities in the UI GreenMetric ranking. As a method for developing the research, it is segregated into two stages. The first comprises the qualitative stage, which has three phases, considered I) Systematic Literature Review (RSL); II) consultation of sustainability reports; III) research with experts in the area of sustainability in universities through a protocol. With the results obtained in this phase, originated useful information for the construction of a research instrument, which is applied in the second stage, called qualitative stage. The second stage, through a survey, sought to understand what are the ESG and SDG practices of 912 universities listed in the UI GreenMetric ranking. The study sample consisted of 106 respondents from different positions in the sustainability area of universities. Data collection occurred by sending the questionnaire in Google Forms to the 42 emails of the universities in the ranking. For data analysis, it was used descriptive analysis (with mean, frequency and standard deviation), confirmatory analysis and data correlation, using the software SPSS - Statistical Package for the Social Sciences. With the results obtained, it was possible to identify that universities are seeking to adopt practices that benefit the environment, society, governance and relationship with stakeholders, promoting sustainability with ESG practices, in view of the actions developed on campus. After the exploratory factor analysis, it was confirmed that several ESG practices correlate with each other and with the SDGs, which indicates that universities seek to align practices towards the goals of the 2030 Agenda. Universities make significant efforts on behalf of society and students, so that education is reached to everyone in a fair and effective way, and they rely on governance, through discussion in boards and promoting stakeholder engagement, to foster debates about sustainability. Nevertheless, it is necessary that they seek to give more attention to the evaluation and monitoring of the efforts made both in ESG practices and in the SDGs, which the institutions work more intensely to promote quality education, gender equality, water and sanitation, and 56 work and economic growth. Finally, a framework is presented, with 7 main elements relevant to the adoption of sustainability practices, both ESG and SDGs identified, which help universities in the adoption of practices towards sustainable development.